Design of AC Charging Interface and Status Acquisition Circuit for Electric Vehicles - Kun Xu; Li Li (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
To address the unreliable charging of new charging interfaces caused by comprehending deviation on China’s alternating current (AC) charging interface standard for electric vehicles, implementation methods of AC charging interface circuit, control pilot (CP) circuit, and status acquisition circuit for electric vehicles were proposed in this study. Basic principle and functions of the CP circuit were discussed, and influences of resistance parameters on voltage state at test point were analyzed. Freescale MC9S12XEQ512 was used as the main controller, and its integrated pulse-width modulation module and analog-to-digital converter module were used to simplify circuit designs. An experimental test on charging interface connection confirmation, CP, output power parameter passing, and real-time charging connection status acquisition was conducted on real vehicles. Results demonstrated that the designed circuits exhibit high security and meet the basic requirements of GB/T20234-2 with regard to AC charging interface characteristics. All test data are within the allowed error range. Furthermore, real-time monitoring of the charging process and security isolation design of signals can effectively improve the system stability. Hence, this technology can be used in AC charge control of electric vehicles.